2017
DOI: 10.1038/srep45051
|View full text |Cite
|
Sign up to set email alerts
|

High-rate squeezing process of bulk metallic glasses

Abstract: High-rate squeezing process of bulk metallic glasses from a cylinder into an intact sheet achieved by impact loading is investigated. Such a large deformation is caused by plastic flow, accompanied with geometrical confinement, shear banding/slipping, thermo softening, melting and joining. Temperature rise during the high-rate squeezing process makes a main effect. The inherent mechanisms are illustrated. Like high-pressure torsion (HPT), equal channel angular pressing (ECAP) and surface mechanical attrition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The crystal size and strain rate can influence the tensile properties of a single crystal Ni3Sn4 via MD simulation [16,19]. Studies have shown that the strain rate affects the tensile properties of the materials, and the UTS of the material increases with the increase in the strain rate [20][21][22][23][24][25]. The results of previous studies were primarily based on experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal size and strain rate can influence the tensile properties of a single crystal Ni3Sn4 via MD simulation [16,19]. Studies have shown that the strain rate affects the tensile properties of the materials, and the UTS of the material increases with the increase in the strain rate [20][21][22][23][24][25]. The results of previous studies were primarily based on experiments.…”
Section: Introductionmentioning
confidence: 99%